P1.33 Multiplex assay for the detection of syphilis and other pathogens associated with genital lesions using plexpcr. (8th July 2017) - Windsor, Madeline; Njuguna, Peter; Tucker, Rachel; Wee, Rachel; Tan, Litty; Azzato, Franca; Mokany, Elisa
Abstract : Introduction: Syphilis is a well-known STI caused by the bacterium Treponema pallidum . It can result in genital lesions and substantial morbidity and mortality. Recently, there has been an alarming global resurgence of syphilis with infections rising to unprecedented rates. As such, it is increasingly pertinent to test genital lesions for syphilis.Herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) and Varicella zoster virus (VZV) cause lesions in cutaneous and mucocutaneous sites. While HSV-1 and HSV-2 are commonly known to cause genital lesions, recent publications have also found VZV in genital specimens. This unexpected finding suggests that reactivation of VZV in this atypical presentation is not as uncommon as previously believed. Using our highly specific PlexZyme technology that enables efficient multiplexing in real-time PCR (qPCR), we have developed a genital lesion assay for the detection of syphilis, HSV-1, HSV-2 and VZV to facilitate prompt and correct treatment of these STI pathogens. Methods: To develop a genital lesion assay, the syphilis target was added to our existing HSV-1, HSV-2 and VZV assay (also containing a DNA extraction/amplification control) in a single-well multiplex qPCR. The performance of the assay was evaluated on 90 genital specimens for which in-house PCR results for syphilis had been determined. Results: The genital lesion assay showed robust performance in multiplex with sensitive detection to 10 copies for all targets. The multiplexed assay detected 54/57 syphilis positives, corresponding to a sensitivity and specificity of 94.7% and 100.0%, respectively. The assay also detected 4 HSV-1 and 2 HSV-2 infections (2 and 1 syphilis co-infections, respectively). Conclusion: The lesion assay offers simultaneous detection and differentiation of pathogens that cause genital lesions. In response to the current emerging syphilis outbreak, this assay could provide a rapid and effective method of determining the infectious agent responsible for genital lesions, supporting earlier detection and rapid treatment to reduce morbidity or worse outcomes.